Key Factors Influencing Bacillus cereus Contamination in Hot Ready-to-Eat Meal Delivery - Komprda, Tomáš; Cwiková, Olga; Kumbár, Vojtěch; Franke, Gabriela; Kouřil, Petr; Patloka, Ondřej; Kameník, Josef; Dušková, Marta; Zouharová, Alena (Foods (Basel, Switzerland), 2025)
With increasing popularity of food delivery services, the microbial safety of transported meals should be ensured. An effect of the type of a meal (cooked rice; mashed potatoes; mushroom sauce), inner primary packaging (sugarcane bagasse [SB] tray; polypropylene [PP] tray), secondary container (polyester/polyethylene foam/aluminum foil [PPA] bag; PP box) on the time interval of the internal hot ready-to-eat (RTE) meal temperature decrease to the value critical for Bacillus cereus growth (40 °C) was tested during a simulated delivery; in aliquot samples of the same meals, B. cereus growth was quantified presuming a natural contamination of the meals. Type of a meal had no effect on the tested time interval (p > 0.05). Packaging a meal in the PP tray as compared to the SB tray and inserting primary trays into the PP box instead of PPA bag delayed (p < 0.05) the internal meal temperature decrease by 50 and 15 min, respectively. Average B. cereus counts in the naturally contaminated meals after the four-hour culturing at 40 °C was 2.99 log CFU·g-1. It was concluded that a hot RTE meal delivered up to four hours under the tested conditions is not likely to facilitate B. cereus growth above unacceptable levels.
Keywords: polypropylene; cooked rice; food safety; pathogenic bacteria; sugarcane bagasse